Safety and efficacy of nipocalimab in adults with generalised myasthenia gravis (Vivacity-MG3): a phase 3, randomised, double-blind, placebo-controlled study - Antozzi, Carlo; Vu, Tuan; Ramchandren, Sindhu; Nowak, Richard J; Farmakidis, Constantine; Bril, Vera; De Bleecker, Jan; Yang, Huan; Minks, Eduard; Park, Jin-Sung; Grudniak, Mariusz; Smilowski, Marek; et al. (Lancet neurology, 2025)
BACKGROUND: Given burdensome side-effects and long latency for efficacy with conventional agents, there is a continued need for generalised myasthenia gravis treatments that are safe and provide consistently sustained, long-term disease control. Nipocalimab, a neonatal Fc receptor blocker, was associated with dose-dependent reductions in total IgG and anti-acetylcholine receptor (AChR) antibodies and clinically meaningful improvements in the Myasthenia Gravis Activities of Daily Living (MG-ADL) scale in patients with generalised myasthenia gravis in a phase 2 study. We aimed to assess the safety and efficacy of nipocalimab in a phase 3 study. METHODS: Vivacity-MG3 was a phase 3, randomised, double-blind, placebo-controlled, phase 3 study conducted at 81 outpatient centres with expertise in myasthenia gravis in 17 countries in Asia-Pacific, Europe, and North America. Adults (aged ≥18 years) with generalised myasthenia gravis inadequately controlled with standard-of-care therapy (MG-ADL score ≥6) were randomly assigned (1:1) to either nipocalimab (30 mg/kg loading dose then 15 mg/kg every 2 weeks for maintenance dosing) or placebo infusions every 2 weeks, added to standard-of-care therapy in both groups, for 24 weeks. Randomisation was stratified by antibody status, day 1 MG-ADL total score, and region. The sponsor, investigators, clinical raters, and participants were masked to treatment assignment. The primary endpoint was the difference between nipocalimab and placebo based on least-squares mean change from baseline in MG-ADL total score averaged over weeks 22, 23, and 24 in the intention-to-treat population of patients who were antibody-positive (for AChR, anti-muscle-specific tyrosine kinase [MuSK], or anti-low-density lipoprotein receptor-related protein 4 [LRP4]). Adverse events were assessed in patients who received at least one dose of study drug. This study is registered at ClinicalTrials.gov, NCT04951622; the double-blind phase is completed and an open-label extension phase is ongoing. FINDINGS: Between July 15, 2021, and Nov 17, 2023, 199 patients were enrolled, and 196 patients received study drug (98 in the nipocalimab group and 98 in the placebo group); of these, 153 (77 in the nipocalimab group and 76 in the placebo group) were antibody-positive. The least-squares mean change in MG-ADL score from baseline to weeks 22, 23, and 24 was -4·70 (SE 0·329) in the nipocalimab group versus -3·25 (0·335) in the placebo group (difference -1·45 [95% CI -2·38 to -0·52]; p=0·0024). The incidence of adverse events was similar between groups (82 [84%] of 98 in both the nipocalimab and placebo groups), including infections (42 [43%] of 98 in the nipocalimab group and placebo group) and headache (14 [14%] of 98 in the nipocalimab group and 17 [17%] of 98 in the placebo group). Serious adverse events were reported for nine (9%) of 98 patients in the nipocalimab group and 14 (14%) of 98 patients in the placebo group, three of which had a fatal outcome (nipocalimab: myasthenic crisis; placebo: cardiac arrest and myocardial infarction). INTERPRETATION: Results from the completed double-blind phase of Vivacity-MG3 support the role of nipocalimab, added to standard-of-care therapies, as a safe treatment for sustained disease control over 6 months for a broad population of patients with generalised myasthenia gravis who are antibody-positive. The ongoing open-label extension phase should provide longer term sustained safety and efficacy data with nipocalimab. FUNDING: Janssen Research & Development, LLC, a Johnson & Johnson company.
Keywords: senioři; dvojitá slepá metoda; činnosti denního života; Double-Blind Method; Receptors, Cholinergic; receptory cholinergní; lidé; výsledek terapie; Middle Aged; mužské pohlaví; myasthenia gravis; Adult; Activities of Daily Living; ženské pohlaví; Humans; Antibodies, Monoclonal, Humanized; Myasthenia Gravis; lidé středního věku; dospělí; Female; Aged; Treatment Outcome; humanizované monoklonální protilátky; Male